Incidence of dentinal crack formation during root canal preparation with two NiTi instruments activated by adaptive motion and continuous rotation: an in vitro study - Erkan, Erhan; Olcay, Keziban; Eyüboğlu, Tan Fırat; Gündoğar, Mustafa (The European Research Journal, 2019)
Objectives: The aim of this study was to evaluate dentin crack incidence after root canal instrumentation using ProTaper Next (PT Next; Dentsply Maillefer, Ballaigues, Switzerland) and Twisted File Adaptive (TF Adaptive; Sybron Endo, Orange, California, USA) at different kinematics. Methods: Sixty human extracted premolar teeth were selected and divided into 4 main groups. Group 1: PT Next with continuous rotation (n = 15); Group 2: PT Next with adaptive motion (n = 15); Group 3: TF Adaptive with continuous rotation (n = 15); Group 4: TF Adaptive with adaptive motion (n = 15). Fifteen unprepared teeth were used as control group. Crowns of the teeth were removed and roots were sectioned at 3, 6, and 9 mm from the apex using a diamond saw. Finally root dentin pieces were evaluated under stereomicroscope at x25 magnification. Digital images were evaluated by 2 researchers. Results: No cracks were observed in the control group. In groups 2 and 4 no fracture was observed at the level of 9 mm and similarly in group 4 at 6 mm level. Group 3 showed a signiﬁcantly higher dentin crack formation followed by Group 1, 2, 4 and control group respectively (p < 0.039). There was no significant difference between groups at 6 mm and 9 mm levels (p = 0.497) except for only 3 mm level (p < 0.035). Conclusions: It was concluded, both adaptive motion and continuous rotationpromoted dentinal defect. Adaptive motion produced less dentinal defects all dentin levels but there was no significant difference.